THE FORMATION OF GNEISSES IN THE SOUTHERN EAST URALIAN ZONE-A RESULT OF LATE PALAEOZOIC GRANITE ASCENT AND EMPLACEMENT - Görz I.; Kroner U.; Ivanov K.S. (My University, 2006)
Geochemical and radiogenic age data are incompatible with the idea that the gneiss-complexes of the East Uralian Zone are microcontinental blocks that collided with the Magnitogorsk island arc during the Uralian orogeny. Field and microstructural data from the Dzhabyk and Suunduk complexes presented in this paper enable us to suggest an alternative model that interprets the gneisses as deformed margins of the batholiths of the Uralian Granite Axis. The gneisses have been formed from a granitic protolith by a continuous fabric transformation on a retrograde metamorphic path. All structures in the gneisses can be assigned to the ascent and emplacement of batholiths in an active strike-slip belt. © 2005 Elsevier Ltd. All rights reserved.
Keywords: EAST URALIAN ZONE; GRANITE-GNEISS COMPLEXES; MAGMA ASCENT; METAMORPHISM